Analisis Risiko K3 Pekerja Alat Container Crane Menggunakan Metode HIRARC Di PT. Pelindo Terminal Petikemas New Makassar (Window of Public Health Journal, 2025)
Every workplace has a risk of workplace accidents. In general, workplace accidents are caused by two factors, namely human actions that do not meet work safety standards and environmental conditions that do not meet safety standards. Accident prevention efforts can be carried out by identifying potential risks. The general objective of this study is to conduct an analysis of Occupational Health and Safety (K3) risks using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method on Container Crane Workers at PT Pelindo Terminal Petikemas New Makassar in 2024. The type of research conducted is quantitative research. Sampling in this study used total sampling with the same number of samples as a sample of 30 respondents. Hazard identification is carried out by conducting interviews and observations of container crane workers. In contrast, risk assessment is carried out by distributing questionnaires assessing the level of possibility and severity of the risk of each potential hazard. After knowing the risk index, risk control is then determined. Based on the research results, 10 potential sources of danger were obtained for container crane workers with a potential danger of 66.7%, risk assessment based on four work steps where work step 1 was 86.7% with a high-risk category and work step 2 was 83.3% with a low-risk category, work steps 3 and 4 were included in the low-risk category. Controls that can be carried out to reduce risk include using Personal Protective Equipment (PPE) for workers and administrative controls.